Penambahan Sari Buah Dan Rempah Terhadap Sifat Organoleptik, Kapasitas Antioksidan, Total Bakteri Asam Laktat, Serta Daya Terima Black Soyghurt (Yoghurt Kedelai Hitam) - Gusti Ayu Kade Widya Diastini; I Ketut Swirya Jaya; I Gde Narda Widiada; Made Darawati (Poltekkes Kemenkes Mataram, 2020)
Background : In Indonesia, not only yellow soybeans are cultivated, but black soybeans are also cultivated and used as industrial food. Soy-based products generally have a weakness that is odor (beany flavor). But it can be overcome by giving flavor to processed soy products, such as fruit juices and herbs. Adding juice and spices to black soybean yoghurt can add flavor to products that have this unpleasant beany flavour. Objectives : To determine the effect of the addition of juice and herbs on organoleptic properties, antioxidant activity, total lactic acid bacteria, and the acceptability of black soyghurt. Methods : The method of data collection is done by analyzing various literatures related to the thesis title. The data source used is secondary data that is data obtained from other people's research literature. The study design was observational and analyzed descriptively. Results : Some juices such as pineapple, dates fruit, jamblang, lakum, guava, soursop, and beetroot and cinnamon were added as natural flavorings to soy yoghurt. And affect the organoleptic properties of soybeans which have odor, and the more additions of fruit and spices, the higher the antioxidant activity and total lactid acid bacteria in yogurt. Conclusion : There are various types of fruit and spices that can be added to soy yogurt and affect the organoleptic properties, antioxidant capacity, total lactic acid bacteria, and acceptability of soy yogurt as a functional drink